A Collaborative Robot for Tea Harvesting with Adjustable Autonomy. Issue 1 (2nd January 2022) - Lai, Yang-Lun; Chen, Po-Lun; Su, Tsung-Chen; Hwang, Wei-Yang; Chen, Shih-Fang; Yen, Ping-Lang
Abstract: A collaborative mobile robot has been developed for tea plucking in narrow terrain tea gardens. The robot executes stable side-by-side motions and carries most of the load of the tea harvesting machine. The robot is controlled with adjustable autonomy so that the human can provide a supervisory role and adjust the optimal height and forward speed of the cutting tool. During tea plucking, the robot can autonomously detect the tree rows and avoid colliding with the trees. The experimental results show that the proposed collaborative robot can stably co-work with humans and significantly improve working efficiency and comfort.